Spectral and electrochemical halide anion recognition by acyclic ruthenium(II) 5,5'-bisamide substituted bipyridyl receptor molecules - Beer, P; Fletcher, N; Wear, T (1996)
A series of new acyclic ruthenium(II) 5,5′-bis-amide substituted 2,2′-bipyridyl receptor molecules have been synthesized. 1H NMR spectroscopy, cyclic and square wave voltammetry, electronic absorption and fluorescence-emission spectroscopic measurements have demonstrated the spectral and electrochemical recognition of chloride, and spectral recognition of bromide anions in polar solvents.